ANALISIS KOMPARATIF SISTEM ERP UNTUK USAHA KECIL MENENGAH (UKM) RETAIL MENGGUNAKAN METODE TOPSIS - Abdul Azis Al Baehaqi; Supriyono; Soni Adiyono (LPPM Universitas Abdurrab, 2026)
Retail SMEs in Indonesia face significant challenges in selecting the right Enterprise Resource Planning (ERP) system due to budget constraints, limited human resources, and lack of systematic evaluation guidance. This research develops a desktop-based decision support system using Python 3.12 with the Flet framework, implementing the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to assist retail SMEs in interactively selecting optimal ERP. The research analyzes seven ERP alternatives (SAP Business One, Oracle NetSuite, PeopleSoft, webERP, Compiere, Odoo, and Accurate Online) using eight main criteria with 26 sub-criteria covering Cost, Functionality and Integration, Time and Availability, Usage and Support, Data Management, Reputation and Strategy Vendor, System Quality, and Scalability. Criteria weights are established referring to systematic literature review with System Quality (0.254) and Data Management (0.248) as highest priorities. Each alternative was assessed based on a review of official vendor documentation, verified review platforms, and relevant academic literature. Analysis results show Odoo ranks first (Ci* = 0.7668), followed by Accurate Online (Ci* = 0.6985), indicating the superiority of open-source and local solutions in cost, system quality, and flexibility for Indonesian retail SME context. The developed decision support system provides practical contribution for retail SMEs in strategic ERP selection decision-making while offering an adaptive evaluation framework for various industry contexts.